Dangal as Experienced by Barangay Workers in the Context of the Pandemic - Abad, Maria Angelica D; Echivarre, Rosanne Marie G; Engay, Bryan Q; Lavides, Maria Margarita R; Terol, Eden H; Tiangco, Cristabel F (Department of Public Administration, 2024)
This work investigated the dangal (dignity) of barangay workers amid the COVID-19 pandemic in the Philippines. The study aimed to know what is dangal for barangay workers during the pandemic, what factors enhanced and limited their dangal, and how can their dangal be promoted. This research is significant due to lack of studies about the personnel serving in barangays - the smallest local government unit in the country. Barangay officials, employees, and volunteers were interviewed, and their responses were evaluated based on themes. Analysis of data revealed that barangay workers had to face several risks and challenges amid their longing to fulfill their duties and responsibilities as public servants. They employed various coping mechanisms although such were insufficient to adequately promote their dignity. Dangal for barangay workers has external and internal domains. The external domain is comprised of their physiological needs and social identity. In the internal domain, dangal is affected by self-fulfillment in performing duties and responsibilities, especially through pakikipagkapwa or the provision of services and assistance to community members. To promote the barangay worker’s dangal; national, provincial, city, and municipal policies must be implemented. For the external domain, remuneration, compensation, benefits, and recognition must be provided. For the internal domain, it is critical that they thrive in an environment that discourages corruption and support actions that reflect honor, excellence, and integrity.